2015
DOI: 10.1080/11250003.2015.1061615
|View full text |Cite
|
Sign up to set email alerts
|

The echinoderm innate humoral immune response

Abstract: Multicellular organisms have an immune system, which is essential for the survival of living beings. Interest in the immune system has been expanded since common characteristics of innate immunity between Drosophila melanogaster (Meigen, 1830) and mammals were discovered in the 1980. Since then, immunology has mainly focused on the adaptive immune system that seems to be restricted to vertebrates. Unlike the innate immunity, the adaptive one is acquired after exposure to a specific antigen (Ag) and includes: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…They possess an innate immune system that acts through humoral and cellular responses. The cellular response is mediated by a particular class of cells, the immune cells, that circulate in the coelomic cavity and can infiltrate tissues and organs; they act through different activating pathways in response to host invasion, insult and cytotoxic agents (Chiaramonte & Russo, ; Pinsino & Matranga, ; Smith et al., ). Since the appearance of the first eukaryotic cells on Earth, many defence mechanisms have evolved to ensure cell integrity, homeostasis and organ survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They possess an innate immune system that acts through humoral and cellular responses. The cellular response is mediated by a particular class of cells, the immune cells, that circulate in the coelomic cavity and can infiltrate tissues and organs; they act through different activating pathways in response to host invasion, insult and cytotoxic agents (Chiaramonte & Russo, ; Pinsino & Matranga, ; Smith et al., ). Since the appearance of the first eukaryotic cells on Earth, many defence mechanisms have evolved to ensure cell integrity, homeostasis and organ survival.…”
Section: Discussionmentioning
confidence: 99%
“…Many echinoderms have been used as model systems for studies on immunology as well as cell and developmental biology (Chiaramonte & Russo, ; Smith et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Matranga et al [19] found elevated red spherula counts in Paracentrotus lividus urchins with spineless lesions covering 10 to 20% of the body whereas mechanical damage is known to increase ceolomocyte number and humoral molecule expression [20]. While many studies have investigated the immune response in sea urchins [21][22][23], few have considered the impact of spine damage on immune function and bacteremia.…”
Section: Introductionmentioning
confidence: 99%
“…The echinoderm immune system consists of cellular and humoral components (Chiaramonte & Russo, ; Ramírez‐Gómez & García‐Arrarás, ; Smith & Davidson, ; Smith et al, ). Cellular defense comprises various types of coelomocyte with humoral defenses mediated by numerous immune‐specific molecules (Chiaramonte & Russo, ; Ramírez‐Gómez & García‐Arrarás, ; Smith et al, ). The axial organ of the coelom is the only organ currently believed to play a role in immune response in echinoderms (Millott, ), possibly through coelomocyte production (Endean, ; Ramírez‐Gómez & García‐Arrarás, ).…”
Section: Introductionmentioning
confidence: 99%
“…As deuterostomes, echinoderms are close relatives of vertebrates. Because of their close phylogenetic association, greater knowledge of the immune systems of echinoderms might help elucidate the evolution and nature of vertebrate immune systems (Chiaramonte & Russo, ; Ramírez‐Gómez & García‐Arrarás, ; Smith & Davidson, ).…”
Section: Introductionmentioning
confidence: 99%